1995
DOI: 10.18174/njas.v43i4.563
|View full text |Cite
|
Sign up to set email alerts
|

The effect of nitrogen and the method of application on the yield of cauliflower

Abstract: The effects of nitrogen on cauliflower yields were studied over a period of 3 seasons at several locations. The cultivar used was Fremont in some cases and Plana in others. Different amounts of N fertilizer were applied at planting and were broadcast or band placed. Another treatment consisted of a split application. The number of plants harvested was not consistently influenced by the amount of N or the method of application. N application influenced the size of the marketable curd. At high yields, band place… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
1

Year Published

1999
1999
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 0 publications
0
1
1
Order By: Relevance
“…With cauliflower and white cabbage a linear relation was found between the optimum nitrogen application and the amount of mineral nitrogen in the soil layer 0-60 cm at planting (Everaarts & De Moel, 1995;Everaarts & De Moel, 1998). Probably the main reason for not finding such a relation for broccoli are the low amounts of mineral nitrogen at planting in the present experiments and the limited variation in amounts between the experiments.…”
Section: Discussioncontrasting
confidence: 58%
See 1 more Smart Citation
“…With cauliflower and white cabbage a linear relation was found between the optimum nitrogen application and the amount of mineral nitrogen in the soil layer 0-60 cm at planting (Everaarts & De Moel, 1995;Everaarts & De Moel, 1998). Probably the main reason for not finding such a relation for broccoli are the low amounts of mineral nitrogen at planting in the present experiments and the limited variation in amounts between the experiments.…”
Section: Discussioncontrasting
confidence: 58%
“…Band placement of nitrogen fertilizer has been mentioned as a possible strategy to increase the yield of Brassicas or to obtain the same yield with less fertilizer (Everaarts, 1993b). However, for cauliflower and white cabbage it was concluded that band placement cannot be recommended (Everaarts & De Moel, 1995;Everaarts & De Moel, 1998). In the analysis of the combined experiments with broccoli a consistent positive effect of band placement on yield was found.…”
Section: Discussionmentioning
confidence: 97%